Investigating Undergraduate Students’ Attitudes Towards English Mobile Learning - Omari, Otmane; Bourekkadi, S.; Slimani, K.; Khoulji, S; Kerkeb, M.L (Transactions on Engineering and Computing Sciences, 2017)
The increase of mobile devices, the availability of several features, and the decrease in terms of cost of smartphones made them useful not only for communication, but also for learning. Similarly, the importance of English in higher education makes it one of the most fundamental foreign languages that students want to learn. Many students look for different ways to learn English. Among these ways is Mobile Learning which becomes nowadays a useful tool for language learning due to the evolution of mobile technology. However, little is known about the attitudes of Moroccan students towards English M-learning. Thus, the purpose of this study is to examine the attitudes of using M-learning by university students to learn English. The study involved 286 students representing different universities, levels, and departments. A questionnaire was distributed and interviews were carried out to answer the research questions. Results revealed that university students have positive attitudes towards English M-learning. The total average mean score obtained for the used scale was M=3.80. Additionally, the qualitative findings confirmed some results of the quantitative data and displayed other important findings related to feelings and obstacles towards English M-learning. The findings are of great importance for teachers, practitioners, administrators, and websites/apps programmers.